The role of alemtuzumab in chronic lymphocytic leukaemia patients with p53 defects (Hematology Meeting Reports, 2009)
Among the biological prognostic factors so far identified in chronic lymphocytic leukaemia (CLL), the most powerful predictor of short survival is mutation or deletion of the TP53 gene at 17p13, which encodes the p53 protein. p53 is a transcription factor that regulates cell growth and survival, contributes to the action of DNA-damaging chemotherapy, and plays a pivotal role in maintaining genomic integrity. TP53 defects are rare at diagnosis but more common in patients with progressive and chemo-resistant disease. Furthermore, p53 dysfunction can arise through alternative mechanisms such as inactivation of ATM, which activates p53 in response to double-strand DNA breaks, or extrinsic suppression of the p53 pathway by basic fibroblast growth factor, which is abundant in the CLL-cell micro-environment. However, mutation or loss of p53 itself is associated with the worst prognosis. Such patients do badly due to rapid clonal expansion, clonal instability and resistance to chemotherapy. Fortunately, two treatments in routine clinical use, glucocorticoids and alemtuzumab, have established activity against p53-defective CLL and work independently of p53. Although each of these agents has its limitations, it is hoped that these can be overcome by using both agents in combination. Early data involving alemtuzumab in combination with high-dose methylprednisolone look promising, and this approach is being formally investigated within the NCRI CLL206 trial. A similar study involving alemtuzumab in combination with dexamethasone is under development by the German CLL Study Group.